2015
DOI: 10.11113/jt.v77.6876
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Altitude and Microclimate on the Distribution Ferns in and Urban Areas

Abstract: The aim of the research is to explore the potential of fern species as natural ecological indicator agent to forecast microclimate changes in the urban area. Ferns which also known as pteridophyte are not only valuable in term of its ethno-botanical uses such as food and medicine but also useful in ecological values. Other than that it can be used to treat unhealthy environment such as absorbing methane gas, fertilizing land and treating heavy metal such as arsenic as well as can be used as a potential ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The higher fern species richness and diversity observed at Bukit Hijau forest than Sungai Sedim could be due to high shade, high humidity, and low light intensity, which characterize tropical primary forests (Anthony et al, 2016). Most of the ferns are shade-and high moisture-loving plants and consequently will prefer more shady forest to open forest (Othman, Latiff, Tukiman, & Hashim, 2015). However, our observation is subjective, as there was no quantitative measurement of these microclimatic conditions.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The higher fern species richness and diversity observed at Bukit Hijau forest than Sungai Sedim could be due to high shade, high humidity, and low light intensity, which characterize tropical primary forests (Anthony et al, 2016). Most of the ferns are shade-and high moisture-loving plants and consequently will prefer more shady forest to open forest (Othman, Latiff, Tukiman, & Hashim, 2015). However, our observation is subjective, as there was no quantitative measurement of these microclimatic conditions.…”
Section: Resultsmentioning
confidence: 92%
“…Also, a higher Simpson index of the Bukit Hijau forest indicated that it is dominated by several fern species with higher incidences across the forest. The lushness of ferns in a forest could be an indicator of the stability and quality of such forest (Beukema & van Noordwijk, 2004;Othman et al, 2015). Moreover, the presence of ferns could also be used to assess the suitability of forests as habitats for other plant functional groups (Duque et al, 2005;Large & Braggins, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…The environmental variables used for the species distribution modelling included the bioclimatic and elevation variables. We decided to use the bioclimatic variables because the occurrence and distribution of ferns are generally influenced by microclimatic conditions especially light intensity, temperature and humidity in their respective habitats (Othman, Latiff, Tukiman, & Hashim, ). Therefore, we based our model on general reports that bioclimatic factors do influence the productivity of plant species in an environment and also influence their distributions at local and global scales (Gogol‐Prokurat, ; Lennon, Greenwood, & Turner, ).…”
Section: Methodsmentioning
confidence: 99%
“…According to Saharizan et al (2021), the diversity and abundance of ferns in an oil palm plantation are dependent the environment, the age of the host, and the agronomic practices applied. In addition, elevation significantly impacts fern distribution (Othman et al 2015), with Saharizan et al (2021) showing that terrestrial pteridophytes are more frequent in oil palm plantations at lower elevations. It supported the findings of this study, where pteridophyte species were substantially less numerous in SM (583 m a.s.l.)…”
Section: Epiphytes Abundancementioning
confidence: 99%